Analisis Kinerja Keuangan Berdasarkan Rasio Arus Kas pada PT Primarindo Asia Infrastructure, Tbk. Tahun 2015 – 2019 Yang Terdaftar di Bursa Efek Indonesia - Dedi Karmana; Sakti Muda Nasution; Mira Ismirani Fudsy (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aims to determine how the financial performance based on the cash flow ratio at PT Primarindo Asia Infrastructure, Tbk. 2015 – 2019 Listed on the Indonesia Stock Exchange. The research method used is a quantitative method where after all the required data has been collected, the next step is to analyze the collected data to be understood and processed in the form of explanations. After analyzing and discussing the problem, the authors conclude that the cash flow ratio shows poor financial performance, because the average ratio decreases and is below 1. There are only 2 ratios that are considered good, namely the operating cash flow ratio to interest and cash flow ratio operations to capital expenditures.